Formation of multiple combustion fronts in an imbert downdraft gasification reactor - Kittipass Wasinarom; S. Sungworagarn; P. Sathitruangsak; Kasemsil Onthong (E3S Web of Conferences, 2021)
The experimental study of downdraft gasification was performed in this paper. The operation which led to the formation of the second combustion front was pointed out. In this situation, both combustion fronts will lose their intensity and finally be extinguished. The operation was unintentionally stopped. It was revealed that the combustion front propagated upward in the reactor after starting the test. While it was about to reach the air inlet nozzle, the second combustion front was detected by an abrupt temperature rise of the thermocouple above the air supply nozzle. After the formation of the second combustion front, both fronts started to lose their intensity which indicated by the decrease in temperature corresponding with their locations. It was possible that the second combustion front would dilute the oxygen concentration supplied to the first combustion front. The decreasing temperature of the first combustion front reduced the heat transfer rate to the second combustion front. Finally, both combustion fronts were extinguished. The operation was unintentionally stopped.
Keywords: Coal Combustion and Slurry Processing; Fire dynamics and safety research; Environmental and Industrial Safety